Characteristics of Lightning Within Electrified Snowfall Events Using Lightning Mapping Arrays. Issue 4 (27th February 2018) - Schultz, Christopher J.; Lang, Timothy J.; Bruning, Eric C.; Calhoun, Kristin M.; Harkema, Sebastian; Curtis, Nathan
Abstract: This study examined 34 lightning flashes within four separate thundersnow events derived from lightning mapping arrays (LMAs) in northern Alabama, central Oklahoma, and Washington DC. The goals were to characterize the in‐cloud component of each lightning flash, as well as the correspondence between the LMA observations and lightning data taken from national lightning networks like the National Lightning Detection Network (NLDN). Individual flashes were examined in detail to highlight several observations within the data set. The study results demonstrated that the structures of these flashes were primarily normal polarity. The mean area encompassed by this set of flashes is 375 km 2, with a maximum flash extent of 2, 300 km 2, a minimum of 3 km 2, and a median of 128 km 2 . An average of 2.29 NLDN flashes were recorded per LMA‐derived lightning flash. A maximum of 11 NLDN flashes were recorded in association with a single LMA‐derived flash on 10 January 2011. Additionally, seven of the 34 flashes in the study contain zero NLDN‐identified flashes. Eleven of the 34 flashes initiated from tall human‐made objects (e.g., communication towers). In at least six lightning flashes, the NLDN detected a return stroke from the cloud back to the tower and not the initial upward leader. This study also discusses lightning's interaction with the human‐built environment and provides an example of lightning within heavy snowfall observed by Geostationary Operational Environmental Satellite‐16's Geostationary Lightning Mapper. Plain Language Summary: This article shows the three‐dimensional structure of lightning within heavy snowfall events. Nearly a third of all lightning events observed in this study originate from tall human‐built objects. Several of these lightning flashes have been observed to occur on spatial scales up to 2, 300 km 2 and come to ground in multiple locations along the lightning path. Key Points: Thirty‐four lightning flashes in heavy snowfall events were examined using lightning mapping arrays Nearly one third of lightning flashes in the four snowfall events examined initiated from tall human‐built objects The lightning flashes examined were spatially extensive, contained multiple ground points, and mostly exhibited normal polarity structures